Female Brown Long‐Eared Bats (Plecotus auritus) Delay Roost Emergence at Elevated Natural Light Conditions - Mari A. Fjelldal; Jonathan Wright; Thomas M. Lilley; Rune Sørås; Clare Stawski (Ecology and Evolution, 2025)
ABSTRACT Nocturnal animals inhabiting northern latitudes face prolonged periods of reduced foraging times in summer due to short light nights. The energetic challenges of reduced foraging times are further heightened in reproductive mammals that allocate substantial resources to offspring care with peak energy demands in mid‐summer. However, little is known about responses to variation in natural light conditions at high latitudes in light‐averse species, such as slow‐flying gleaning bats, especially during reproduction. Here, we investigate the impacts of natural light levels and other environmental conditions (i.e., temperature, rain and wind) on individual‐level activity patterns (emergence time, return time, proportion of night utilised) in reproductive and non‐reproductive female brown long‐eared bats, Plecotus auritus (Nind = 27) in Norway (60.1° N) collected across three summers (2019–2021). We found that bats delayed the start of evening foraging trips on lighter nights, typically emerging from the roost only when light levels decreased below 5 lux, likely because higher light levels are associated with increased predation risk. However, no such effect was found in morning return times to the roost, for which bats showed greater light tolerance. Lactating females took apparently higher risks and left the roost approximately 20 min earlier than non‐reproductive females, presumably because of their greater energetic requirements. They also spent a larger proportion of the night away from the roost compared to pregnant and non‐reproductive individuals, although this proportion was influenced by variation in environmental conditions, such as temperature, rainfall and windspeed. Our results highlight the dynamic nature of responses in light‐averse bats balancing risks of predation against foraging gains during reproduction at northern latitudes. Reduced foraging times during short northern nights may thus represent a hard constraint to range expansion in slow‐flying gleaning bats, even if other environmental conditions improve with climate change.